1990
DOI: 10.1203/00006450-199002000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Derived Relaxing Factor: Presence in Pulmonary and Systemic Arteries of the Newborn Guinea Pig

Abstract: ABSTRACT. Endothelium-derived relaxing factor (EDRF), believed to be nitric oxide or a compound that releases nitric oxide, is a potent vasodilator produced by some arteries in response to acetylcholine (ACh) and bradykinin (BK). ACh and BK are potent dilators of perinatal pulmonary and systemic arteries. The objectives of this study were to determine if EDRF is present in newborn vessels and if EDRF mediates the vasodilator actions of ACh and BK. Arterial rings from newborn guinea pigs, 1 to 3 d old, were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 13 publications
0
20
1
Order By: Relevance
“…In addition to its key role in vascular reactivity, experimental studies have shown that the endothelium may also be important for long-term arterial remodeling and in the control of elastic properties of the arterial wall. 31,32 Damage to the endothelium in large arteries has been shown not only to impair active diameter changes 33 but also to increase the viscosity of the arterial wall. 32 A total of 10 of 32 eligible LBW subjects were lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its key role in vascular reactivity, experimental studies have shown that the endothelium may also be important for long-term arterial remodeling and in the control of elastic properties of the arterial wall. 31,32 Damage to the endothelium in large arteries has been shown not only to impair active diameter changes 33 but also to increase the viscosity of the arterial wall. 32 A total of 10 of 32 eligible LBW subjects were lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These other mechanisms most likely involve the vasodilator peptide, bradykinin, which is produced by the lungs during oxygenation (21). Bradykinin may exert its effect either directly or by stimulating endotheliumderived relaxing factor, a potent vasodilator (20) produced by the endothelium of pulmonary arteries of newborn guinea pigs (22). Although bradykinin effects also may be mediated by PGs (23), this specific mechanism is unlikely to be of major importance during the transitional period, based on the findings of this study.…”
Section: Discussionmentioning
confidence: 81%
“…The Society for Behavioral Pediatrics will conduct its 9th Annual Scientific Meeting and Workshops on September [21][22][23]1991 …”
Section: Announcementmentioning
confidence: 99%
“…from the pulmonary artery and descending aorta of 1-to 3-d-old guinea pigs. The dilator action of bradykinin on pulmonary artery rings in vitro was attributed primarily to EDRF (14). In the present study, we examined whether EDRF plays an important role in the neonatal lung microvasculature as a vasoactive substance that controls neonatal pulmonary vascular resistance.…”
Section: Protocol 2 Ejfkct Of High-dose Nma Alone Afier Bradykinininmentioning
confidence: 99%
“…A very recent report suggests that EDRF synthesis may contribute to the decrease of pulmonary vascular resistance that occurs at birth ( 13), but it is not known whether impaired EDRF activity is involved in the pulmonary hypertension associated with a variety of neonatal lung diseases, such as persistent pulmonary hypertension of the newborn and bronchopulmonary dysplasia. In previous work (14), we demonstrated the presence of EDRF in isolated vascular rings from the pulmonary artery and descending aorta of the newborn guinea pig. One finding was that in vitro, bradykinin, a putative mediator of the pulmonary hernodynamic adjustments at birth (l5), relaxed the preconstricted neonatal pulmonary artery ring by an EDRFdependent mechanism.…”
mentioning
confidence: 99%